Laparoscopic closure of the pouch of Douglas by a peritoneal running suture. A minimally invasive and prosthetic-free technique to prevent excessive dose delivery to the small bowel during pelvic irradiation for prostate cancer. (January 2021) - Loo, Maxime; Martinez-Gomez, Carlos; Khalifa, Jonathan; Angeles, Martina-Aida; Chira, Ciprian; Piram, Lucie; Martin, Elodie; Malavaud, Bernard; Ferron, Gwenaël; Graff-Cailleaud, Pierre
Highlights: The radiation tolerance of the small bowel is limited. Chronic radiation-induced enteritis affects patients quality of life. Ectopic small bowel loops trapped in the pelvis may challenge prostate radiotherapy. A laparoscopic prosthetic-free technique to cordon off bowel loops from the pelvis. Abstract: Background and purpose: Prostate radiotherapy relies on the delivery of high doses that can be obstructed when a small bowel loop descends in the pelvis. We present a laparoscopic minimally invasive prosthetic-free technique closing the Douglas' pouch with a peritoneal running suture to cordon off the bowel from the pelvis and hence allow optimal irradiation. Materials and methods: Prostate cancer patients referred for radiotherapy and whose planning-CT revealed a bowel loop trapped in the pelvis were proposed the procedure, followed by a new planning-CT. This proof-of-concept study reports postoperative follow-up and dosimetric benefits. Results: The procedure was performed in ten patients (2016–2020) as a same-day surgery for nine. Median operative time was 34 min (range 22–50) and no relevant intraoperative complication occurred. The third patient of the series presented a small bowel hernia through the peritoneal suture at the 15th postoperative day requiring a laparotomic desincarceration without major consequences. Regarding the small bowel, median D1cc (dose to 1 cc) was 65.5 Gy and 55.5 Gy (p = 0.005) before and after procedure. Median V60 (volume receiving ≥60 Gy) was 10.2 cc and 0.0 cc (p = 0.005). In the immediate vicinity of the small bowel (5 mm), median D1cc was 68.3 Gy and 57.7 Gy (p = 0.005). Radiotherapy was safely delivered to all patients. Conclusion: Laparoscopic closure of the Douglas' pouch by a peritoneal suture is an efficient technique to cordon off inconvenient ectopic small bowel loops. It prevents excessive bowel irradiation and hence facilitates curative prostate radiotherapy. The technique could be applied to other pelvic malignancies.